Splinter hemorrhages as a possible sign of myocardial infarction and pulmonary embolism - Đorđević, Stefan; Anđelić, Slađana (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Introduction/Objective: Subungual splinter hemorrhages are a common clinical sign, usually associated with illnesses of different severity. We present a patient with chest pain where differential diagnosis could be both MI and PE, and on whose skin we could note SSH. Case report: An emergency team was sent to a 58yo patient because of chest pain. Patient gives information of a chest pain with no propagation, that started a few hours ago. ECG: sinus rhytm, S1 in D1, ST elevation in D2, D3 and aVF ≤1mm, ST depression V4 – V6. SSH were noted on nail beds. The patient was transported to the cardiology unit where by continious observation troponin T and creatin kinaze were increasing. Because of elevated value for D dimer and pulmonary artery’s MSCT the patient was suspected to have pulmonary embolism as well. Conclusion: Future studies should focus on defining links between SSH with MI and PE.